2015
DOI: 10.1586/17476348.2015.1103650
|View full text |Cite
|
Sign up to set email alerts
|

Electrical impedance tomography: functional lung imaging on its way to clinical practice?

Abstract: Electrical impedance tomography (EIT) has the potential to become a bedside tool for monitoring and guiding ventilator therapy as well as tracking the development of chronic lung diseases. This review article summarizes recent publications (from 2011) dealing with the applications of pulmonary EIT. Original papers on EIT lung imaging in clinical settings are analyzed and divided into several categories according to the lung pathology of the study subjects. Studies on children and infants are presented separate… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
37
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
5
2

Relationship

2
5

Authors

Journals

citations
Cited by 46 publications
(41 citation statements)
references
References 87 publications
0
37
0
1
Order By: Relevance
“…After decades of research, electrical imperdance tomography (EIT) is now commercially available to monitor the pattern of regional ventilation of the lungs during mechanical ventilation, and to show how it changes by modifying ventilation mode and parameters [61]. Recent studies showed that EIT can be an effective tool to titrate optimal PEEP [6265].…”
Section: Adjusting Mechanical Ventilation For Patients’ Condition Andmentioning
confidence: 99%
“…After decades of research, electrical imperdance tomography (EIT) is now commercially available to monitor the pattern of regional ventilation of the lungs during mechanical ventilation, and to show how it changes by modifying ventilation mode and parameters [61]. Recent studies showed that EIT can be an effective tool to titrate optimal PEEP [6265].…”
Section: Adjusting Mechanical Ventilation For Patients’ Condition Andmentioning
confidence: 99%
“…Electrical impedance tomography (EIT) is a non‐invasive, highly dynamic tool that also provides regional functional information on lung ventilation. Although the high correlation between EIT and aeration of the lung during tidal breathing is well documented, EIT is still mainly used to provide information on lung aeration in intensive care settings to improve mechanical ventilation . However, preliminary studies have shown a similar correlation between EIT and aeration during forced expiration maneuvers when performing spirometry and during forced oscillation maneuvers .…”
Section: Introductionmentioning
confidence: 99%
“…Electrical Impedance Tomography (EIT) is an imaging technique which is used in a clinical context to monitor impedance changes caused by conductivity‐contrasting liquid and gasses, such as those caused by cancer, brain ischemia, or ventilation. One main area of application is to generate tomographic images of the regional lung ventilation . EIT utilizes changes in electrical impedance of lung tissue during breathing.…”
Section: Introductionmentioning
confidence: 99%
“…One main area of application is to generate tomographic images of the regional lung ventilation. 1 EIT utilizes changes in electrical impedance of lung tissue during breathing. Expansion of the alveoli during inspiration hinders the flow of electrical currents and as a result increases the electrical impedance.…”
Section: Introductionmentioning
confidence: 99%